Analisis Yuridis Putusan Mahkamah Agung Tentang Penyelesaian Sengketa Perbuatan Melawan Hukum Dalam Perjanjian Kredit Dengan Hak Tanggungan - Zahri, Ilham; Yahya, Azhari; Adli, M. (Jurnal Suara Hukum, 2023)
There are 2 (two) similar cases with the identical subject matter but decided differently by the Supreme Court, as contained in Supreme Court Decision No. 353 K/Pdt/2015 dated June 22, 2015, and Supreme Court Decision No. 1228 K/Pdt/2018 June 23, 2018.The purpose of this research is to find out the legal considerations by the Panel of Judges of the Supreme Court in those cases and to conduct a review of the two decisions according to the perspective of legal objectives. This type of research is normative juridical law research. This research shows that the Decision of the Supreme Court of the Republic of Indonesia Number 353 K/Pdt/2015 dated June 22, 2015, has correctly considered the the provisions of Article 8 of the Collateral Law. Meanwhile, the Decision of the Supreme Court of the Republic of Indonesia Number 1228 K/Pdt/2018 dated June 23, 2018, has ignored Article 8 of the Collateral Law by considering the errors of Defendant I and Defendant II in binding the collateral. So from this research, it was found that the legal considerations of the Panel of Judges in decision Number 1228 K/Pdt/2018 dated June 23, 2018, were not following the perspective of the legal objectives.